Analysis of passenger rolling stock faults and its statistics in Lithuania - Gelumbickas, Gintaras; Vaičiūnas, Gediminas (Transport, 2011)
Performed data analysis aims to determine the number of rolling stock breakdowns and how it depends on rolling stock age, the number of passengers and operations. The mathematical model, stated below, analyses correlation between passenger fleet upgrade intensity and the number of faults. When planning to buy some new rolling stock (3÷6 wagons electric or diesel trains) while using this model, the number of faults can be predicted up to five years.First Published Online: 05 Oct 2011